Geotechnical properties of mixtures of water treatment sludge and residual lateritic soils from the State of São Paulo. - Tejeda Montalvan, Edy Lenin (2020)
The most common practices for disposal of water treatment sludge (WTS) have generally been dumping into rivers, disposal in sanitary landfills, and discharge in sewage treatment plants. However, growing environmental concern and rigorous legislation have led to the search for more adequate disposal or recycling alternatives, such as, reuse in ceramic products, cement production, agriculture, earthworks, among others. Reuse of WTS in earthworks is a promising alternative, since large amounts of soil are used, which can be partly substituted by WTS as long as engineering properties are not significantly altered. This research investigated the geotechnical behavior of soils and WTS mixtures in different blending ratios in order to evaluate their suitability for geotechnical structures, as material for embankments, backfills, and bottom liners and covers of landfills. The studied soils and sludges comprise a lateritic clayey sand, a lateritic clay, a ferric sludge, and an alum sludge. Both sludges were chemically and mineralogically characterized by x-ray diffraction, x-ray fluorescence, scanning electron microscopy, loss on ignition, pH, cation exchange capacity, and organic matter. Geotechnical characterization of the soils and sludges comprised grain-size distribution, specific gravity of solids, and Atterberg limits. Each soil was mixed with each sludge at three different blending ratios, thus twelve mixtures were prepared. The geotechnical behavior of the mixtures was evaluated by the following tests: standard-effort Proctor compaction, oedometric compression, consolidated undrained triaxial compression, permeability, and unconfined compression. Moreover, volumetric shrinkage and soil-water retention tests were conducted. Besides, analyses by mercury intrusion porosimetry were carried out.Compelling results were obtained. Most of the mixtures presented compressibility and shear strength suitable for earthworks. Some mixtures presented adequate permeability for landfill liners, and all mixtures could be used as daily cover material in landfills. The final step for reuse would be the environmental evaluation of the mixtures, which was not in the scope of this thesis; apropos, physical-chemical characterization of the sludges indicates that environmental risk associated to release of contaminants is not to be expected. The results indicate that, from a structural point of view, WTS can be incorporated to local soils for geotechnical applications, provided the feasible mixtures are evaluated by means of typical geotechnical testing and criteria coherent with the intended application.